Prognostic Value of Cerebroplacental Ratio in Appropriate-for-Gestational-Age Fetuses Before Induction of Labor in Late-Term Pregnancies - Ortiz, Javier U.; Graupner, Oliver; Flechsenhar, Sarah; Karge, Anne; Ostermayer, Eva; Abel, Kathrin; Kuschel, Bettina; Lobmaier, Silvia M. (Ultraschall in der Medizin - European Journal of Ultrasound, 2021)
Purpose To evaluate the relationship between cerebroplacental ratio (CPR) and the need for operative delivery due to intrapartum fetal compromise (IFC) and adverse perinatal outcome (APO) in appropriate-for-gestational-age (AGA) late-term pregnancies undergoing induction of labor. The predictive performance of CPR was also assessed.Materials and Methods Retrospective study including singleton AGA pregnancies that underwent elective induction of labor between 41 + 0 and 41 + 6 weeks and were delivered before 42 + 0 weeks. IFC was defined as persistent pathological CTG or pathological CTG and fetal scalp pH < 7.20. Operative delivery included instrumental vaginal delivery (IVD) and cesarean section (CS). APO was defined as a composite of umbilical artery pH < 7.20, Apgar score < 7 at 5 minutes, and admission to the neonatal intensive care unit for > 24 hours.Results The study included 314 women with 32 (10 %) IVDs and 49 (16 %) CSs due to IFC and 85 (27 %) APO cases. Fetuses with CPR < 10th percentile showed a significantly higher rate of operative delivery for IFC (40 % (21/52) vs. 23 % (60/262); p = 0.008) yet not a significantly higher rate of APO (31 % (16/52) vs. 26 % (69/262); p = 0.511). The predictive values of CPR for operative delivery due to IFC and APO showed sensitivities of 26 % and 19 %, specificities of 87 % and 84 %, positive LRs of 2.0 and 1.2, and negative LRs of 0.85 and 0.96, respectively.Conclusion Low CPR in AGA late-term pregnancies undergoing elective induction of labor was associated with a higher risk of operative delivery for IFC without increasing the APO rate. However, the predictive value of CPR was poor.
Keywords: appropriate-for-gestational-age; late-term pregnancy; intrapartum fetal compromise; adverse perinatal outcome; cerebroplacental ratio